The Impact of Job Demands and Spirituality on Employee Engagement: Evidence from Christian Lecturers in Indonesia - Brahmana, Karina Meriem Beru; Pasaribu, Ronald Panaehan; Rosito, Asina Christina; Sinaga, Arnanda Parozi; Zai, Ribka Rahayu (Journal of Educational, Health and Community Psychology, 2025)
This study investigated the influence of job demands and spirituality on employee engagement, focusing on Christian lecturers in Indonesia. The research is both timely and significant, as it offers a fresh perspective on the typically negative association between job demands and employee engagement. Contrary to conventional assumptions, the findings reveal that job demands can, in fact, enhance work engagement among Christian lecturers, particularly when accompanied by a strong sense of spirituality. Employing a quantitative correlational design, data were collected from 200 lecturers selected through purposive sampling. Employee engagement was measured using the Utrecht Work Engagement Scale, while job demands and spirituality were assessed using established and validated instruments. Data analysis was conducted using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results demonstrated that job demands had a positive effect on employee engagement, indicating that greater work demands were linked to higher levels of engagement. This finding offers a novel contribution, as it deviates from much of the prior literature. In alignment with the Job Demands-Resources (JD-R) model, the study suggests that under certain conditions, job demands can be reinterpreted as challenges that stimulate motivation and foster engagement, particularly when supported by sufficient job resources. Furthermore, spirituality emerged as a significant predictor of employee engagement, underscoring the importance of meaning and purpose in strengthening lecturers’ dedication to their work. Overall, these findings affirm the JD-R model and highlight the need to balance job demands with both organizational and personal resources, including spiritual well-being. Future studies are encouraged to explore these dynamics across different religious contexts and consider other external factors influencing employee engagement.